2014
DOI: 10.1093/molehr/gau086
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA in Day 3 embryo culture medium is a novel, non-invasive biomarker of blastocyst potential and implantation outcome

Abstract: In assisted reproduction technology, embryo competence is routinely evaluated on morphological criteria. Over the last decade, efforts in improving non-invasive embryo assessment have looked into the secretome of embryos. Human embryos release genomic DNA (gDNA) and mitochondrial DNA (mtDNA) into the culture medium, and the mtDNA/gDNA ratio is significantly correlated with embryo fragmentation. Here, we investigate whether mtDNA/gDNA ratio in embryo spent medium is correlated with blastulation potential and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 68 publications
2
73
2
1
Order By: Relevance
“…This process is aided by the shedding of mtDNA during preimplantation development (Stigliani et al 2014). This suggests that these variants provide a positive functional role during early development but, as they may be potentially lethal later in life, they are subsequently reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This process is aided by the shedding of mtDNA during preimplantation development (Stigliani et al 2014). This suggests that these variants provide a positive functional role during early development but, as they may be potentially lethal later in life, they are subsequently reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The replication of mitochondrial DNA is under dynamic regulation during pre-implantation development (Cagnone et al 2016) and stress responses could trigger the release of this DNA into the culture medium (due to cell death or clearance of damaged mitochondria). Recent studies have shown that an increased copy number of the mtDNA genome in embryonic cells and in spent media is a sign of a metabolic response to developmental stress (Stigliani et al 2013(Stigliani et al , 2014.…”
Section: Mitochondrial Signallingmentioning
confidence: 99%
“…Palini et al (23) reported the observation of the existence of DNA in the blastocoele fluid, Gianaroli et al (24) performed a pilot study on chromosome screening using blastocentesis, and Stigliani et al (25,26) observed genomic and mitochondria DNA contents in the culture medium, which were correlated with embryo quality. Wu et al (27) reported the PCR detection of the secreted genomic DNA in the culture medium for preimplantation…”
mentioning
confidence: 99%